Chronic and acute pancreatitis elastography - current knowledge - Agnieszka M. Sepioł; Maciej M. Cebula (Śląski Uniwersytet Medyczny w Katowicach, 2023)
This paper is a review of available studies concerning the topic of ultrasound elastography as a modality for diagnosing chronic or acute pancreatitis. Twenty-eight articles published between 2004 and 2022 containing keywords related to elastography and acute and chronic pancreatitis were reviewed using databases and search engines such as PubMed, Scopus, Google Scholar and Web of Science. Acute and chronic pancreatitis increase the stiffness of the pancreatic parenchyma, which can be measured using strain or shear wave elastography. Numerous studies have shown promising results, and it seems that it is possible to use elastography as a routine technique in the diagnosis of chronic or acute pancreatitis. Nevertheless, certain limitations such as age or body weight, should be considered when performing elastography.